An evidence based approach towards optimising the management of patients with squamous cell carcinoma of the skin - Lansbury, Louise E. (2014)
Cutaneous squamous cell carcinoma (SCC) is a common cancer yet its treatment is under-researched. The objective of this thesis was to develop a proposal for a randomised controlled trial (RCT) to address uncertainties relating to the management of the condition, and to ultimately improve the management of affected patients.